Optimization of Inulin Extraction from Chicory Roots and an Ultrafiltration Application to Obtain Purified Inulin and Hydrolyzed Fructooligosaccharides - Sagcan, Nihan; Sagcan, Hasan; Bozkurt, Fatih; Gunes, Ayse Nur Bulut; Fakir, Huseyin; Dertli, Enes; Sagdic, Osman (ANKARA UNIV, FAC AGRICULTURE, 2024)
Inulin and fructooligosaccharides (FOS) are prominent functional components in the food industry due to prebiotic and other pharmaceutical properties. Inulin is a storage polysaccharide in various plants. FOS are naturally present in various plants and can be obtained by partial hydrolysis of inulin. In this study, ground and sieved chicory roots (Cichorium intybus L.) were used as starting material for inulin extraction under optimized conditions determined by Response Surface Methodology (RSM) with a Box-Behnken design. Optimum inulin extraction conditions from chicory roots were; temperature of 90 degrees C, extraction time of 30 min., and liquid -to -solid (LS) ratio of 10:1 mL/g. Inulin extract was further hydrolyzed to FOS by enzymatic or acid treatment, separately. Purification of inulin extract and FOS hydrolysate was performed by ultrafiltration with a 10 kDa membrane under the pressure of 2 bar with continuous stirring. As a result, inulin and FOS were obtained at 90% and 76% purity, respectively.
Keywords: Cichorium intybus; fructooligosaccharides; Response surface methodology; HPLC-RID analysis; Acid-enzyme hydrolysis; Membrane filtration; CICHORIUM-INTYBUS L.; JERUSALEM-ARTICHOKE; FRUCTO-OLIGOSACCHARIDES; LIQUID-CHROMATOGRAPHY; ENZYMATIC-HYDROLYSIS; ASSISTED EXTRACTION; IN-VITRO; Agriculture